COLLECTIVE MENTALITIES IN THE SYSTEM OF CULTURAL DETERMINANTS OF SOCIAL COMPETENCE - VARETSKA, OLENA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article substantiates the importance of the development of social competence in the process of globalization. It outlines the author's view on the influence of collective mentalities in the system of socio-cultural determinants, researches the opinions of scholars on the essence of mentality, individual and group mentality, nation and ethnos mentality. It covers the features of ethnic Ukrainians, their inherent trait enabling to consolidate around the national idea.